Implementasi Algoritma AES Pada QR-Code Sebagai Parameter Keaslian Data Dalam Pembuatan KTA - Nahar Mardiyantoro; Mefa Listiani (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
The process of making KTA at UPT RPH Wonosobo Regency which is still carried out by typing prospectivemember data in MS Excel and editing it in the form of a card and then be printed, is considered ineffective so that it prolongs the process of making KTA. Besides that there is no guarantee of authenticity, so an application for making KTA is made with added the AES algorithm to speed up the performance of the KTA manufacturing process and guarantee its authenticity. The implementation of the AES Algorithm is included in the KTA checking URL which is converted into a QR-Code for easy scanning. This research is expected to help the process of making KTA at UPT RPH Wonosobo Regency and ensure the authenticity of the KTA made.